Does gaming keep subjects awake?: Subjective and objective sleep parameters following gaming in comparison to a passive control - Klier, Kristina; Alesi, André; Herhaus, Benedict; Keller, Marius; Hardt, Jochen; Brixius, Klara; Froböse, Ingo; Wagner, Matthias; Petrowski, Katja (Physiology & behavior, 2024)
•Getting sufficient and restful sleep following gaming seems to be possible.•Gaming as a leisure activity does not necessarily impact health negatively.•Concentration and alertness can be increased by a gaming activity. Gaming is a global phenomenon often associated with impaired health and sleep patterns. Although the research activities are growing, the evidence to date is rare due to the various gaming titles and inconsistent study designs. Thus, this study aimed to examine the impact of excessive gaming in the evening on subjective as well as objective sleep parameters by focusing on specific game titles and assessing several evenings/nights using a mixed-methods approach. A total of 33 experienced young male adults (23.00 ± 3.53 years old, ranked players in League of Legends or Counter-Strike: Global Offensive) took part. The individuals’ sleep parameters were assessed via diary and actigraphy. In randomized order, one week apart and for a duration of 120 min each, two study evenings were spent gaming, while the other two evenings were spent without digital media and gaming, but instead watching a nature documentary. No significant difference between the conditions were found (p > 0.05) in either the sleep duration nor the sleep quality. Daytime sleepiness was significantly increased after watching the documentary movie, when compared to gaming (p < 0.001). These results indicate that, one the one hand, the gaming activity leads to higher arousal and alertness as it requires concentration and dedication. On the other hand, this impact seems only short-term and does not necessarily affect sleep patterns. Future studies are needed to gain deeper insights, especially regarding the long-term health effects of gaming.